2021
DOI: 10.1080/14693062.2021.1878999
|View full text |Cite
|
Sign up to set email alerts
|

The EU ETS to 2030 and beyond: adjusting the cap in light of the 1.5°C target and current energy policies

Abstract: The Paris Agreement calls on countries to pursue efforts to limit global average temperature rise to 1.5°C. We derive a 2016-2050 emission budget for the EU Emissions Trading System (EU ETS) based on cost-effectiveness criteria aimed at achieving the 1.5°C target with a 50%-66% probability, and translate it into a cap reduction path. We show that, under current ETS parameters, the vast majority of this budget will be consumed by 2030. Meeting the budget under current 2030 EU ETS parameters would require drasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…The Phase 4 reforms had taken several important incremental steps, but more ambitious reforms would be required to reach these new targets. Several significant changes were now being considered, including: extending the EU ETS to cover the maritime, road transport, and buildings sectors; overhauling the carbon leakage regime, including the proposal for a Carbon Border Adjustment Mechanism (CBAM); and making a major adjustment to the emissions cap through a one‐off downward adjustment (“re‐basing”) or by further increasing the linear reduction factor (Zaklan et al, 2021). …”
Section: Evolution Of the Eu Etsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Phase 4 reforms had taken several important incremental steps, but more ambitious reforms would be required to reach these new targets. Several significant changes were now being considered, including: extending the EU ETS to cover the maritime, road transport, and buildings sectors; overhauling the carbon leakage regime, including the proposal for a Carbon Border Adjustment Mechanism (CBAM); and making a major adjustment to the emissions cap through a one‐off downward adjustment (“re‐basing”) or by further increasing the linear reduction factor (Zaklan et al, 2021). …”
Section: Evolution Of the Eu Etsmentioning
confidence: 99%
“…• overhauling the carbon leakage regime, including the proposal for a Carbon Border Adjustment Mechanism (CBAM); • and making a major adjustment to the emissions cap through a one-off downward adjustment ("re-basing") or by further increasing the linear reduction factor (Zaklan et al, 2021).…”
Section: Phase 4 2021-2030mentioning
confidence: 99%
“…An interesting point was made by [27], who observed that significant differences between the EU Member States can be identified in terms of ETS implementation, but their research covered only the first phase of the system. A recent scholarly contribution has also demonstrated that a cap adjustment can take place because of increased EU targets for renewable energy and increased energy efficiency, accompanied by policies aimed at eliminating coal from the energy mix at the national level; hence, it was estimated that emissions in the sectors covered by the EU ETS can diminish by 57% until 2030 [28].…”
Section: The Eu Ets Systemmentioning
confidence: 99%
“…It is a cap-andtrade approach in which the cap decreases over time [5] and installation owners can trade allowances following market-based opportunity decisions [6]. With the Green Deal, the European Commission intends to achieve climate neutrality by 2050 [7] boosted by the Fit-for-55 package [8]: a set of proposals to pave the way for decarbonization goals [9]. The package includes major initiatives on effort-sharing regulation [10], land use, forestry, alternative fuel infrastructure, measures aimed at reducing carbon leakage, and ETS.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of a global carbon market can result in carbon leakage, especially if carbon prices are destined to increase to achieve new climate targets [32]; from this perspective, it is worth noting that the carbon price has often been used as an indicator of the effectiveness of the ETS [33]. Some scholars have underlined that the new 2050 targets can be achieved if the ETS parameters are properly updated [8].…”
Section: Introductionmentioning
confidence: 99%